Prehospital management of a non-intubated inhalation injury patient using transcutaneous monitoring of carbon dioxide - Kikuta, Shota (BMJ Case Rep, 2021)
A 46-year-old man experienced facial burns due to a fire in his house. In the prehospital setting, suspecting inhalation injury and carbon monoxide poisoning, an emergency physician decided to bring him to the hospital for carbon dioxide (CO(2)) monitoring without endotracheal intubation for approximately 20 min because of less severe respiratory distress. On the way to the hospital, the patient’s end-tidal CO(2) monitoring ranged from 19 to 30 mm Hg, and transcutaneous carbon dioxide (TcPCO(2)) remained between 50 and 55 mm Hg. On arrival at the hospital, PaCO(2) showed 51.6 mm Hg. Endotracheal intubation using a bronchoscope was performed in the emergency room, and inhalation injury was observed. He was extubated on day 5 and discharged on day 10. In the prehospital setting, TcPCO(2) monitoring is useful for initial management of non-intubated inhalation injury patients even with high concentration oxygen.